2020
DOI: 10.1159/000511868
|View full text |Cite
|
Sign up to set email alerts
|

Coprevalence of Hidradenitis Suppurativa and Psoriasis: Detailed Demographic, Disease Severity and Comorbidity Pattern

Abstract: <b><i>Background and Objectives:</i></b> Hidradenitis suppurativa (HS) and plaque psoriasis (Pso) are supposed to have a coprevalence. However, data showing a more detailed description of patients with both diseases are rare. In this study, we characterized patients with both skin diseases in terms of onset, disease course, severity, concomitant diseases and therapeutical management. <b><i>Patients and Methods:</i></b> Data from 28 patients with a confirmed codia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In a study by Pinter et al. ( 29 ), there was a slight male predominance (1.15:1) with the first symptoms of psoriasis occurring earlier than symptoms of HS. However, for those with HS disease as its first symptoms, the severity of the disease is greater than those patients who started with symptoms of psoriasis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a study by Pinter et al. ( 29 ), there was a slight male predominance (1.15:1) with the first symptoms of psoriasis occurring earlier than symptoms of HS. However, for those with HS disease as its first symptoms, the severity of the disease is greater than those patients who started with symptoms of psoriasis.…”
Section: Discussionmentioning
confidence: 92%
“…The similarity in the cytokines involved may explain the usefulness of biologic therapies in HS. Among biologic therapies, TNF alpha inhibitors such as adalimumab and IL-17 inhibitors such as brodalumab were found to have a positive effect in patients with HS and psoriasis ( 29 , 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, hidradenitis suppurativa (HS) also exhibits a systemic inflammatory nature with systemic comorbidities similar to psoriasis. The systemic inflammation might explain the observation of a recent study, where it was found that in patients with both HS and psoriasis, the disease diagnosed first tended to take a more severe course than the later diagnosed (Figure 2) [33].…”
Section: When Psoriasis Coexists With Other Skin Diseasesmentioning
confidence: 84%
“…The convergence of cytokines implicated in both conditions rationalizes the efficacy of biological therapies for HS. For example, TNF-α inhibitors, such as adalimumab, and IL-17 inhibitors, like brodalumab, have demonstrated beneficial effects in patients with both HS and PSO by targeting common inflammatory mechanisms [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%